A New Biocomposite Material Based on Wheat Waste and Suitable for 3D Printing Applications. Issue 1 (21st October 2022) - Giani, Niccolò; Mazzocchetti, Laura; Benelli, Tiziana; Bovo, Marco; Gazzotti, Stefano; Torreggiani, Daniele; Tassinari, Patrizia; Giorgini, Loris
Abstract: Biopolymers, such as poly(lactic) acid (PLA), which is obtained through green synthesis pathways from renewable resources, has attracted considerable interest in recent years because of the increasing need to reduce petroleum‐based plastic pollution and bringing their prices comparable with conventional thermoplastic commodities' price (e.g., polyethylene, polypropylene, and polystyrene). The present work investigates the employment of 10% wt of natural materials, deriving from wheat milling process, as biofiller of PLA to develop a biocomposite filament suitable for 3D‐printing technique. The inclusion of a cost‐free natural material leads to a strong reduction of the whole material cost. Implementing this new class of composite material to additive manufacturing technique allows to dramatically reduce the environmental impact of 3D printed products.